Bulgarian Open Science Cloud - Stanchev, Peter; Stefanov, Krassen (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
The paper presents the current state of Building the Bulgarian OpenScience Cloud (BOSC).
Keywords: Open Science; European Open Science Cloud; Bulgarian Open Science Cloud